Cloud Driven Variability on Young Brown Dwarfs and Giant Exoplanets. Issue Volume 10:Issue S314(2015) (November 2015) - Biller, Beth
Abstract: Variability has now been robustly observed in a range of L and T type field brown dwarfs, primarily at near-IR and mid-IR wavelengths. The probable cause of this variability is surface inhomogeneities in the clouds of these objects, causing a semi-periodic variability signal when combined with the rotational modulation from the 3-12 hour period expected for these objects. Variability at similar or even higher amplitudes may be expected for young brown dwarfs and giant exoplanets, which share similar Teff as field brown dwarfs, but have considerably lower surface gravities. Variability studies of these objects relative to old field objects is then a direct probe of the effects of surface gravity on atmospheric structure. Here I discuss ongoing efforts to detect variability from these young objects, both for free-floating objects and companions to stars, including preliminary results from an ongoing survey of young, low surface gravity objects with NTT SOFI.